Hemiptera Coccoidea new or little known for the Italian fauna (Bollettino di zoologia agraria e bachicoltura, 2024)
Peliococcus chersonensis (Kiritshenko), Trionymus radicum (Newstead) (Pseudococcidae),Stotzia ephedrae (Newstead) (Coccidae) and Quadraspidiotus mairei(Balachowski) (Diaspididae) are recorded for the first time in Italy. New distributionaldata are reported for Chaetococcus sulcii (Green), Peliococcus manifectusBorchsenius, Phenacoccus asphodeli Goux, Dysmicoccus multivorus (Kiritshenko),Volvicoccus volvifer (Goux) (Pseudococcidae), Protopulvinaria pyriformis Cockerell(Coccidae), Aspidiotus spinosus Comstock, Chionaspis lepineyi Balachowsky,Dynaspidiotus ephedrarum (Lindinger), Adiscodiaspis ericicola (Marchal), Rungaspiscapparidis (Bodenheimer) (Diaspididae).